LEGAL BASIS OF METEOROLOGICAL PROVISION FOR CIVIL AVIATION - Vodolaskova, Kateryna Yu. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: to study domestic legal acts and international standards and rules, which regulates provision of the meteorological services of civil aviation. Research methods: formal-dogmatic, documentary analysis and synthesis, comparative analysis, cognitive-analytical, etc. Results: it was structured the legal fundamental basis for meteorological provision of civil aviation. Discussion: clarified regulatory consolidation of standards and rules in the sphere of meteorological provision of civil aviation, studied the competence of authorized bodies and the content of meteorological services.